Achievement motivation and emotional intelligence in elite female and male wrestlers - Rutkowska, K.; Gierczuk, D. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2020)
Achievement motivation is the tendency to act towards a specific goal attainment that makes it possible to gain personal fulfilment even if it is necessary to surmount some obstacles. According to studies described in the literature of the subject, it is associated with emotional intelligence, which plays an adaptive role. Emotional competences help the individual to cope with different situations. The study sought to diagnose achievement motivation and emotional intelligence and to establish correlations between them in elite female and male wrestlers. The study included 11 female and 64 male Greco-Roman wrestlers aged 16-26. Two comparative groups (11 females and 11 males) were formed for the needs of the comparative analysis. The analysis of research results makes it possible to state that in the examined group of female and male wrestlers, the dimensions of both achievement motivation and of emotional intelligence fall within the range of average results. The study revealed significant differences in the results concerning the levels of achievement motivation in women and men. The men demonstrated higher levels of eagerness to learn, pride in productivity, engagement, competitiveness and flow than the women. An overall result obtained with the use of LMI was also higher in male wrestlers. Furthermore, male competitors were found to exhibit significantly higher levels of ambition. A number of correlations between particular dimensions of emotional intelligence and achievement motivation were noted; however, it also refers to factor results. Intrapersonal emotional intelligence was correlated with self-assurance and self-control, whereas general emotional intelligence was correlated with self-assurance and ambition. It is recommended that psychological training and long-term cooperation with sports psychologists should be implemented in the wrestling training process. Achievement motivation and emotional intelligence are factors that help the individual to cope better with stress/difficult situations both within and outside the sport. The study is a contribution to the discussion on the issue of the professionalization of wrestling in Poland